The Role of Media and Social Movement in Human Rights Issue: The Case of ‘Comfort Women’ by Japan Colonization - Suwardi, Anna C.; Rosydiana, Atina (Indonesian Perspective, 2017)
Many countries in Asia were conquered by Japan during the World War II, including Korea and Indonesia. Romusha, or slavery system introduced by Japan, also imposed to women. Girls were sent to brothels as Jugun Ianfu/‘comfort women’. Differ from men, women got double burdens, both physically and mentally, thus trauma was inevitable. The belief of taboo is also spreading, hence the movement of victims which demands to get their dignity back is rarely found. Using setting agenda theory and social movement theory, this paper argues that the best potential to promote human rights and justice of ‘comfort women’ goes to media. In South Korea, social movement has been advocating people about ‘comfort women’ as forced victims, not a voluntarily choice. Through engaging media, they hope to use its power to persuade people, changing the paradigm that ’comfort women’ were not sexual workers, but victims of war who needs assistance from society to heal their trauma.Keywords: ‘comfort women’, Japan colonization, media, sexual harassment, social movement